Few-mode photonic crystal fibers for mode-converter devices and sensing applications (2019)
One of the major challenges in telecommunications is related with the increase of the transmission capacity of optical links. To carry out this task, several experts recommend the use of spatial division multiplexing alternative since it offers the possibility to multiply the number of available channels or their capacity. In this case, the mode converters play an important role because they are used to control the propagating mode into the optical link. On the other hand, optical fiber sensors are attached the attention and it have been used in many industrial applications due that they offer several advantages compared with traditional technologies. Therefore, in order to satisfy both necessities, in this thesis we explore the possibility to obtain mode converters and optical fibers sensor using hybrid photonic crystal fibers. In fact, we select two specific configurations, the fist one is a Few-Mode PCF with internal electrodes and the second one is an asymmetric dial-core PCF. Both fibers are filled with thermo-sensitive materials to obtain photonic devices with improved characteristics. In the first part of this thesis, a computational methodology that allows the study of photonic devices based on few-mode PCFs with internal electrodes is proposed. In that part, a computational methodology using the finite element method to integrate the thermo-mechanic and electromagnetic phenomena is constructed, which allow to understand the operating principle of this structures and optimize the performance of photonic devices based on this kind of optical fibers. In order to validate the numerical model, two different experiments are carried out. The experimental results show a good mismatch with the predicted with the proposed computational model. In addition, a similar numerical model is constructed to analyze the operating principle of an asymmetrical dual-core transversally chirped PCFs. Likewise, the employed post-processing techniques to obtain these singular PCFs are showed. Afterwards, two different mode converters devices based on two different PCF structures are development. In the first one, a mode converter based on an asymmetric dual-core PCF is proposed and numerically analyzed when the air-holes are filled with a thermo-sensitive liquid material. First, the performance of the mode converter as a function of the microstructure is analyzed, and evidence that the number and the type of modes that interchange energy in this structure depends of the pitch and the diameter of the holes. Next, we demonstrate that controlling the refractive index of the liquid into the air-holes it is possible to obtain a tunable device for the conversion from the LP01 mode to the LP11 mode that can operate in the S + C + L + U bands. Here, the operating wavelength is controlled through thermal changes. The second alternative consists in the use of a Few-mode PCF with internal Indium electrodes. In this part, the capability of this structure to make a controllable, stable, and versatile all-fiber mode converter at 980 nm is studied and analyzed. The experimental study demonstrates the possibility to convert the HE11 mode into the TE01, TM01 and HE21 modes when the FMF-PCF with internal electrodes is heated. The results reveal that the performance of the proposed mode converter depends on the input light polarization, the analyzer angle and the applied temperature. The proposed device presents a compact size of 4 cm and shows high mode conversion efficiency. In fact, it can reach at least 50% of mode conversion efficiency in abroad range of temperatures. Then, both alternatives are suitable to be implemented in spatial division multiplexing systems. Finally, the use of these PCF as sensors is investigated. Firstly, a highly sensitive Sagnac loop interferometer temperature sensor based on metal-filled SH-PCF was investigated. Bismuth and indium metals were used to examine the effect of filler metal on the temperature sensitivity of the fiber-optic temperature sensor. It was found from measurements that a very high temperature sensitivity of −9.0 nm/°C could be achieved with the indium-filled side-hole PCF. The experimental results are compared to numerical simulations with good agreement. It is shown that the high temperature sensitivity of the sensor is attributed to the fiber microstructure, which has a significant influence on the modulation of the birefringence caused by the expansion of the metal-filled holes. On the other hand, an In-line Mach-Zehnder refractive index sensor based on an asymmetrical dual-core transversally chirped PCFs was numerically analyzed. Thus, we demonstrate a suitable structure for label-free detection of molecules. Then, the change of the layer thickness of biomolecules can then be detected as a change in the device transmittance. Numerical calculations indicate that this novel structure can achieve acceptable level of sensitivity whereas the biosensor is mm long.